Monosporium apiospermum meningoencephalitis: a clinico-pathological case. Issue 8 (August 1991) - Durieu, I; Parent, M; Ajana, F; Gosset, P; Smadja, D; Leclerc, X; Fournier, Y; Leys, D
Abstract : Twenty nine cases of central nervous system infection due to Monosporium apiospermum have been reported. Six of them occurred after an aspiration pneumonia following a near drowning. The case of a 53 year old man is reported: M apiospermum was isolated from cerebrospinal fluid, sputum, urine and from the mud of the ditch where the patient had fallen. Though the treatment used recommended doses of intravenous, intrathecal and intraventricular amphotericin B, it was ineffective and the patient died 97 days after the near drowning. Necropsy showed that the ventricular infectious process was more prominent distant from the antifungal ventricular source.